Production method for titanium alloy molded body

The method for manufacturing titanium alloy molded bodies addresses the balance between fatigue and mechanical strength by machining the surface of additive-manufactured primary bodies and then applying a controlled HIP treatment, resulting in enhanced strength and cost-effectiveness.

JP2025056412APending Publication Date: 2025-04-08MITSUBISHI HEAVY IND LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023165869
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The challenge is to develop a method for manufacturing titanium alloy molded bodies that balances fatigue strength and mechanical strength while minimizing the cost of the processing device, particularly by addressing the issue of grain coarsening during HIP treatment.

Method used

The method involves forming a primary metal molded body using a titanium alloy powder through additive manufacturing, machining the surface to remove defects, and then subjecting the secondary metal molded body to a HIP treatment within a temperature range of 800° C. to 890° C., thereby ensuring both fatigue and mechanical strength without increasing pressure resistance and costs.

Benefits of technology

This approach effectively enhances both fatigue strength and mechanical strength of titanium alloy molded bodies while keeping the costs in check by optimizing the HIP treatment conditions to prevent grain coarsening.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056412000001_ABST
    Figure 2025056412000001_ABST
Patent Text Reader

Abstract

To secure both fatigue strength and mechanical strength while suppressing cost increase.SOLUTION: Disclosed is a method for producing a titanium alloy molded body comprising: a step of using a metal powder composed of a titanium alloy and forming a primary metal molded body by laminate molding; a step of removing the surface of the primary metal molded body with a thickness equal to or greater than a predetermined dimension by machining to obtain a secondary metal molded body; and a step of subjecting the secondary metal molded body to hot isostatic pressing (HIP) treatment in a temperature range of 800°C or more and 890°C or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] FIELD OF THE DISCLOSURE The present disclosure relates to methods for manufacturing titanium alloy compacts. [Background technology]

[0002] A configuration has been disclosed in which titanium alloy powder containing titanium (Ti) as the main alloy is used to form an additive manufacturing body having a desired shape by metal powder additive manufacturing (see, for example, Patent Document 1). Furthermore, HIP (Hot Isostatic Pressing) treatment is known as a method for removing internal defects in metal molded products such as castings and sintered bodies (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 2019-73760 [Patent Document 2] Japanese Patent Application Laid-Open No. 2016-112580 Summary of the Invention [Problem to be solved by the invention]

[0004] The inventors have discovered that when HIP treatment is performed on an additive manufacturing body formed by metal powder additive manufacturing using titanium alloy powder, the fatigue strength of the additive manufacturing body is increased by removing internal defects, but mechanical strength such as tensile strength is reduced.The reduction in mechanical strength is thought to be due to the fact that the metal crystal grains forming the additive manufacturing body become coarse as a result of the HIP treatment being performed at a high temperature, for example, above 900°C, in order to fully remove internal defects. On the other hand, if the HIP temperature is lowered, the coarsening of metal crystal grains is suppressed, but the effect of removing internal defects is reduced.

[0005] In contrast, if the HIP treatment temperature is lowered while the pressure is increased, it is expected that the internal defects can be removed while suppressing the coarsening of metal crystal grains. However, increasing the pressure during HIP treatment requires increasing the pressure resistance of the HIP treatment equipment, which leads to an increase in the cost of the treatment equipment.

[0006] The present disclosure has been made to solve the above-mentioned problems, and aims to provide a method for manufacturing a titanium alloy formed body that can ensure both fatigue strength and mechanical strength while suppressing cost increases. [Means for solving the problem]

[0007] In order to solve the above problems, the method for manufacturing a titanium alloy formed body according to the present disclosure includes the steps of: using a metal powder made of a titanium alloy to form a primary metal formed body by an additive manufacturing method; removing the surface of the primary metal formed body by machining to a thickness of at least a predetermined dimension to obtain a secondary metal formed body; and subjecting the secondary metal formed body to a hot isostatic pressing (HIP) treatment in a temperature range of 800°C to 890°C. [Effects of the Invention]

[0008] According to the method for producing a titanium alloy formed body of the present disclosure, it is possible to ensure both fatigue strength and mechanical strength while suppressing increases in cost. [Brief explanation of the drawings]

[0009] [Figure 1] 1 is a flowchart showing the steps of a method for manufacturing a titanium alloy formed body according to an embodiment of the present disclosure. [Figure 2] FIG. 1 is a schematic diagram showing a process for forming a primary metal body by additive manufacturing. [Figure 3] FIG. 2 is a schematic diagram showing a step of removing the surface of a primary metal compact to obtain a secondary metal compact. [Figure 4] This shows the distribution of defects obtained from the X-ray CT inspection results of the test piece before HIP treatment. [Figure 5] FIG. 10 is a diagram showing the distribution of defect occurrence positions in the results of an X-ray CT inspection of a test piece. [Figure 6] FIG. 1 is a diagram showing the relative density of a test piece after HIP treatment. [Figure 7] FIG. 10 is a diagram showing the results of an X-ray CT inspection of a test piece. [Figure 8] FIG. 1 shows the EBSD measurement results and FE-SEM observation results of a test specimen after HIP treatment. [Figure 9] FIG. 1 is a graph showing the relationship between the average lath width of the α phase and the HIP treatment temperature. [Figure 10] FIG. 10 shows the results of a fatigue test on a test piece whose surface has not been removed. [Figure 11] FIG. 1 shows the results of a fatigue test on a test piece with its surface removed. [Figure 12] FIG. 10 is a diagram showing the results of a fatigue test on test pieces with different thicknesses of surface removal. DETAILED DESCRIPTION OF THE INVENTION

[0010] Hereinafter, an embodiment of the method for manufacturing a titanium alloy formed body according to the present disclosure will be described with reference to the accompanying drawings, but the present disclosure is not limited to this embodiment. (Procedure for manufacturing titanium alloy compact) As shown in FIG. 1, the method for manufacturing a titanium alloy formed body includes step S1 of forming a primary metal formed body by additive manufacturing, step S2 of removing the surface of the primary metal formed body to obtain a secondary metal formed body, and step S3 of subjecting the secondary metal formed body to HIP treatment.

[0011] FIG. 2 is a schematic diagram showing the steps of forming a primary metal compact by additive manufacturing. In step S1 of forming a primary metal compact by additive manufacturing, as shown in FIG. 2, a metal powder M made of a titanium alloy is used to form a primary metal compact 101 by additive manufacturing.

[0012] The titanium alloy used as the metal powder M is a Ti-6Al-4V alloy, which contains titanium (Ti) as the main alloy and at least 5.5 to 6.75 mass% aluminum (Al) and 3.5 to 4.5 mass% vanadium (V). In addition to titanium, aluminum, and vanadium, the titanium alloy (Ti-6Al-4V alloy) also contains iron (Fe), oxygen (O), nitrogen (N), and carbon (C). The titanium alloy (Ti-6Al-4V alloy) may further contain additives other than those mentioned above. The metal powder M has an average particle size of, for example, 15 to 45 μm.

[0013] In this embodiment, laser powder bed fusion (L-PBF) is used as the additive manufacturing method. In this method, metal powder M made of the titanium alloy is placed in a material tank 11 to a predetermined thickness to form a powder bed P. A laser beam B is irradiated onto this powder bed P in accordance with the cross-sectional pattern of the primary metal molded body 101 to be formed. The metal powder M in the powder bed P irradiated with the laser beam B melts. When the irradiation of the laser beam B is then terminated, the molten metal solidifies. The process of stacking the metal powder M, irradiating the laser beam B, and solidifying the molten metal is then repeated in the material tank 11, thereby forming a primary metal molded body 101 of a predetermined shape by additive manufacturing. After the primary metal molded body 101 is formed, it is removed from the material tank 11.

[0014] In step S1, a primary metal compact 101 having a relative density of 99.8% or more is formed. A more preferable range for the relative density of the primary metal compact 101 formed in step S1 is 99.9% or more. A particularly preferable range for the relative density of the primary metal compact 101 formed in step S1 is 99.98% or more. Furthermore, it is preferable that the primary metal compact 101 removed from the material tank 11 is subjected to stress relief treatment such as vacuum heat treatment under predetermined conditions.

[0015] FIG. 3 is a schematic diagram showing the process of removing the surface of a primary metal compact to obtain a secondary metal compact. In step S2 of removing the surface of the primary metal compact to obtain a secondary metal compact, as shown in FIG. 3 , the surface 101f of the primary metal compact 101 formed in step S1 is removed by machining to a thickness T equal to or greater than a predetermined dimension. Examples of machining for removing the surface 101f by the thickness T include cutting using a lathe, milling machine, multi-axis machining center, or the like. Here, the thickness T of the surface 101f of the primary metal compact 101 is preferably, for example, 0.1 mm to 1.0 mm. A more preferred range for the thickness T of the surface 101f is 0.15 mm to 0.5 mm. A particularly preferred range for the thickness T of the surface 101f is 0.2 mm to 0.4 mm. In this embodiment, the thickness T of the surface 101f is, for example, 0.3 mm.

[0016] In step S2, surface 101f of primary metal compact 101 is removed in this manner to obtain secondary metal compact 102. In primary metal compact 101 formed by powder bed fusion, minute irregularities and internal defects caused by particles of molten metal powder M tend to concentrate near surface 101f during molding. In step S2, surface 101f of primary metal compact 101 is removed to obtain secondary metal compact 102 from which the minute irregularities and internal defects that occurred near surface 101f in step S1 have been removed.

[0017] In step S3 of subjecting the secondary metal compact to HIP treatment, the secondary metal compact 102 obtained in step S2 is placed in a HIP treatment device (not shown) and subjected to HIP treatment. At this time, the temperature range of the HIP treatment performed on the secondary metal compact 102 is preferably, for example, 800°C or higher and 890°C or lower. A more preferred temperature range for the HIP treatment is 820°C or higher and 880°C or lower. A particularly preferred temperature range for the HIP treatment is 840°C or higher and 860°C or lower. In this embodiment, the HIP treatment is performed at 850°C in step S3.

[0018] Furthermore, the pressure during the HIP treatment in step S3 is preferably 70 MPa or more and 200 MPa or less. A more preferred range for the pressure during the HIP treatment is 80 MPa or more and 150 MPa or less. A particularly preferred range for the pressure during the HIP treatment is 90 MPa or more and 110 MPa or less. In this embodiment, the HIP treatment in step S3 is performed at 100 MPa. By setting the pressure during the HIP treatment within the above range, the cost of the HIP treatment equipment can be prevented from increasing. In this manner, in step S3, the secondary metal compact 102 is subjected to HIP treatment, thereby obtaining the titanium alloy compact 103.

[0019] (Action and effect) In the method for manufacturing a titanium alloy compact having the above configuration, a metal powder M made of titanium alloy is used to form a primary metal compact 101 by additive manufacturing, and the surface 102f of the primary metal compact 101 is machined to a thickness T equal to or greater than a predetermined dimension. This removes defects that have occurred near the surface 102f of the primary metal compact 101. The resulting secondary metal compact 102 is then subjected to a HIP treatment at a temperature range of 800°C to 890°C. This prevents grain coarsening and further removes internal defects without increasing the pressure during the HIP treatment. As a result, both fatigue strength and mechanical strength can be ensured while preventing increases in cost.

[0020] Furthermore, in step S2 of obtaining the secondary metal compact 102, defects occurring near the surface 102f of the primary metal compact 101 can be removed by removing the surface 102f of the primary metal compact 101 to a thickness T of 0.1 mm or more. Furthermore, removing the surface 102f of the primary metal compact 101 to a thickness T of 1.0 mm or less can reduce the time required for machining to remove the surface 102f. This allows defects occurring near the surface 102f of the primary metal compact 101 to be efficiently removed.

[0021] Furthermore, in the HIP process S3, the HIP process is performed in a temperature range of 830°C or higher and 870°C or lower, which makes it possible to more effectively remove internal defects while suppressing the coarsening of crystal grains in the secondary metal molding 102.

[0022] Furthermore, by forming the primary metal compact 101 having a relative density of 99.8% or more in step S1 of forming the primary metal compact 101, it is possible to obtain a primary metal compact 101 with reduced internal defects and a high relative density. Using such a primary metal compact 101 as a base, by grinding the surface 101f and applying HIP treatment, it is possible to efficiently manufacture a titanium alloy compact 103 that ensures both fatigue strength and mechanical strength.

[0023] Furthermore, in the primary metal compact 101 formed using powder bed fusion, defects are likely to occur near its surface 101f. By performing HIP treatment after grinding the surface 101f of such a primary metal compact 101, it is possible to ensure both fatigue strength and mechanical strength in a titanium alloy compact formed using powder bed fusion, which is likely to have defects near its surface 101f.

[0024] Furthermore, in a titanium alloy formed body using Ti-6Al-4V alloy as the titanium alloy, both fatigue strength and mechanical strength can be ensured.

[0025] (Example) Next, the manufacturing method of the titanium alloy form in the above embodiment was verified, and the results are shown below. In the case of titanium alloy, which is an α+β type two-phase alloy, the strength, ductility, toughness, and fatigue strength resulting from heat treatment are inversely related to each other. In addition, the surface condition after fabrication also has a significant impact on fatigue strength. Therefore, in this study, the following evaluations were carried out on a titanium alloy (Ti-6Al-4V) fabricated using laser powder bed fusion.

[0026] As the metal powder M made of titanium alloy, Ti-6Al-4V plasma atomized powder (manufactured by AP&C (Advanced Powders & Coatings, Inc.)) Grade 23, ASTM F3001, particle size: 15 to 45 μm was used. The EOSM290 (manufactured by EOS GmbH) / ProX320 (manufactured by 3D Systems) was used as a molding device to form the primary metal molding 101 by laser powder bed fusion, and the thickness of each layer of metal powder was set to 60 μm.Test pieces corresponding to the primary metal molding 101 were formed in the shape of a round bar and a flat plate. For comparison, we also created test pieces with intentionally high defect rates (hereinafter referred to as defective test pieces) by changing the process parameters (laser output, laser scanning speed, etc.) during manufacturing and manufacturing under conditions that deviated from the standard conditions. After fabrication, each test piece was subjected to stress relief treatment (600°C / 1H: vacuum heat treatment).

[0027] For the test piece before HIP treatment, which corresponds to the formed primary metal molding 101, the defect rate was calculated and the defect size and distribution were investigated using an X-ray CT device (inspeXio SMX-225CT FPD HR: manufactured by Shimadzu Corporation). Figure 4 shows the distribution of defects obtained from the results of X-ray CT inspection of the test piece before HIP treatment. Figure 5 shows the distribution of defect occurrence positions in the results of X-ray CT inspection of the test piece. The defect rate for each test piece was approximately 0.011%. As shown in Figure 4, the majority of the defect sizes were in the 30 to 50 μm range, with the maximum defect size being approximately 85 μm. Furthermore, as shown in Figure 5, it was confirmed that defects K were concentrated near the surface, with many defects occurring within a range of approximately 200 μm from the surface of test piece S. On the other hand, the defective test pieces with a higher defect rate had a cross-sectional defect rate of about 1.24%.

[0028] FIG. 6 is a diagram showing the relative density of the test piece after the HIP treatment. As shown in Figure 6, when the HIP treatment temperature is 780°C or higher and the HIP treatment time is 2 hours or longer, the relative density reaches 99.9% or higher. When the HIP treatment temperature is 830°C or higher, the relative density reaches 99.9% or higher with a shorter HIP treatment time.

[0029] Subsequently, the test piece was subjected to HIP treatment under the following five HIP treatment conditions, Condition 1 to Condition 5. The pressure was 100 MPa in all cases. Condition 1: HIP treatment temperature 850°C, HIP treatment time 2 hours Condition 2: HIP treatment temperature 920°C, HIP treatment time 2 hours Condition 3: HIP treatment temperature 950°C, HIP treatment time 2 hours Condition 4: HIP treatment temperature 920°C, HIP treatment time 4 hours Condition 5: HIP treatment temperature 920°C, HIP treatment time 1 hour On the other hand, the defective test pieces with a high defect rate were subjected to HIP treatment under the above conditions 1 to 3.

[0030] In order to evaluate the defect removal performance for each HIP treatment condition, the cross section of the test piece after HIP treatment was observed using an optical microscope. First, the cross-sectional images of the test pieces were binarized using an optical microscope, and the defect rate of the cross section was calculated. As a result, under all HIP processing conditions, the defect rate of the test pieces was approximately 0.01 to 0.03%, and the defects had almost disappeared visually. On the other hand, in the defective test pieces with a high defect rate, the cross-sectional defect rate was approximately 0.00 to 0.01 regardless of the HIP treatment temperature, and the defects inside the test pieces had almost completely disappeared, while the defects that were presumed to have been open on the surface remained even after HIP treatment.

[0031] Next, the HIP-treated test pieces were inspected using an X-ray CT device, with the test pieces HIP-treated under the conditions of 850°C / 2H as a representative example. Figure 7 shows the results of the X-ray CT inspection of the test piece. As shown in Figure 7, no defects were detected in the entire imaging area of ​​the test piece, and all of the defects, including those that were concentrated near the surface of the test piece, had disappeared. On the other hand, in the defective test pieces with a high defect rate, no defects were detected inside the test pieces, but it was confirmed that defects that opened on the surface of the test pieces remained.

[0032] Next, to investigate the differences in material structure due to HIP processing conditions, the test specimens were observed using an EBSD (Electron Backscattered Diffraction Pattern) electron microscope and an FE-SEM (Field Emission Scanning Electron Microscope). FIG. 8 shows the EBSD measurement results and FE-SEM observation results of the test piece after the HIP treatment. As shown in Figure 8, the results of EBSD measurements showed that the higher the HIP treatment temperature, the larger the size of the α phase in the material structure of the test specimen. As for the β phase, the higher the HIP treatment temperature and the longer the holding time, the larger the size and the higher the phase fraction tended to be. Prior β grains can be roughly identified based on the crystal orientation of the α and β phases using the Burgers' orientation relationship, but almost no difference in prior β grain size was observed depending on the HIP treatment conditions. Furthermore, FE-SEM observations revealed a tendency for the α-phase size to increase with increasing HIP temperature. For specimens subjected to HIP treatment at 920°C with varying holding times, almost no difference in the α-phase size was observed, suggesting that almost no grain growth of the α-phase occurred.

[0033] Furthermore, the relationship between the average lath width of the α phase and the HIP treatment temperature was calculated by image processing the FE-SEM image shown in Figure 8. Fig. 9 shows the relationship between the average lath width of the α phase and the HIP treatment temperature. As shown in Fig. 9, the Arrhenius plot showed linearity between the average lath width of the α phase and the HIP treatment temperature, which suggests that the grain growth rate of the α phase is diffusion-limited.

[0034] Next, the effect of removing the surface was confirmed for the HIP-treated test pieces. First, a fatigue test was performed on the test specimens that had been HIP-treated under conditions 1 to 5 without removing the surface. The fatigue test was performed by applying a stress ratio of R=0.1, a waveform of a constant amplitude sine wave, and a frequency of 10 to 15 Hz to the test specimens, with a fatigue limit of 2 × 106 cycles. FIG. 10 shows the results of a fatigue test on a test piece whose surface was not removed. As shown in FIG. 10, the test piece under condition 1, which was subjected to HIP treatment at 850° C., tended to have a slightly lower fatigue strength than the other test pieces under conditions 2 to 4, but no significant difference was observed. When the fracture surfaces of the specimens that broke in the fatigue tests were observed, it was confirmed that the fracture origins were all in uneven areas of the surface shape or surface defects (lack of fusion), and that the surface condition had a significant influence. In particular, no differences in the fracture surface condition were observed depending on the HIP processing conditions.

[0035] Next, before the HIP treatment, test pieces were prepared by removing approximately 2.5 mm of the surface by machining, and the HIP treatment was carried out under conditions 1 to 5. The same fatigue test as above was carried out on each test piece after the HIP treatment. FIG. 11 shows the results of a fatigue test on a test piece with its surface removed. As shown in FIG. 11, the test specimens with the surface removed had fatigue strength equivalent to that of general materials under all conditions 1 to 5, and the fatigue limit (defined as 2 × 10 cycles) tended to be condition 1 (HIP treatment temperature: 850°C) > conditions 2, 4, and 5 (HIP treatment temperature: 920°C) > condition 2 (HIP treatment temperature: 950°C). In particular, it was confirmed that the fatigue strength was clearly improved under condition 1, where the HIP treatment temperature was 850°C. When the fracture surfaces of the specimens that had broken in the fatigue tests were observed, no clear defects were found at the fracture origin in any of the specimens, confirming that the fracture was due to the microstructure. From these results, it was also confirmed that defects at a level that would affect fatigue strength had disappeared under all HIP treatment conditions from Condition 1 to Condition 5.

[0036] Next, test specimens were prepared with the surface removed to different thicknesses of 0.1, 0.2, and 0.3 mm, and after HIP treatment, fatigue tests were carried out in the same manner as above, under the HIP treatment conditions of Condition 2 (HIP treatment temperature 920°C, HIP treatment time 2 hours). FIG. 12 shows the results of fatigue tests on test pieces with different thicknesses of surface removal. As shown in Figure 12, it was confirmed that the fatigue strength tends to increase as the thickness of the surface removed increases. When the thickness of the surface removed was 0.3 mm, it was confirmed that the fatigue strength was almost equivalent to that of general materials. When observing the fracture surfaces of specimens that broke in fatigue tests, a correlation was found between the size of the defect at the fracture origin and the fatigue strength. When the thickness of the surface removed was 0.1 mm, all fractures originated from defects. When the thickness of the surface removed was 0.2 mm, fractures were a mixture of defect-originating specimens and specimens with fractures caused by the microstructure. When the thickness of the surface removed was 0.3 mm, no clear defects were found at the fracture origin in any of the specimens. This confirmed that by limiting the thickness of the surface removed to 0.2 to 0.3 mm, it is possible to effectively eliminate defects near the surface that are introduced during manufacturing and are a factor that affects fatigue life.

[0037] These results clearly show that by ensuring that the thickness of the surface removed is 0.3 mm or more, the influence of the surface layer can be eliminated and the effects of HIP treatment can be obtained.

[0038] <Additional Notes> The method for producing a titanium alloy formed body described in each embodiment can be understood, for example, as follows.

[0039] (1) A method for producing a titanium alloy molded body according to a first aspect includes a step S1 in which a metal powder M made of a titanium alloy is used to form a primary metal molded body 101 by an additive manufacturing method; a step S2 of removing a surface 101f of the primary metal compact 101 by machining to a thickness T equal to or greater than a predetermined dimension to obtain a secondary metal compact 102; and step S3 of subjecting the secondary metal compact 102 to a hot isostatic pressing (HIP) treatment in a temperature range of 800°C or higher and 890°C or lower.

[0040] This method for producing a titanium alloy compact involves forming a primary metal compact 101 by additive manufacturing using a titanium alloy metal powder M. The primary metal compact 101 is then machined to remove a thickness T greater than or equal to a predetermined dimension, thereby eliminating defects that have developed near the surface 101f of the primary metal compact 101. The resulting secondary metal compact 102 is then subjected to a HIP process at a temperature between 800°C and 890°C, thereby further eliminating internal defects while suppressing grain coarsening and without increasing the pressure during the HIP process. As a result, both fatigue strength and mechanical strength can be ensured while suppressing increases in cost.

[0041] (2) A second aspect of the method for producing a titanium alloy formed body is the method for producing a titanium alloy formed body of (1), in which in step S2 for obtaining the secondary metal formed body 102, the surface 101f of the primary metal formed body 101 is removed to a thickness T of 0.1 mm or more and 1.0 mm or less.

[0042] As a result, in step S2 of obtaining the secondary metal compact 102, surface 101f of primary metal compact 101 is removed to a thickness T of 0.1 mm or more, thereby removing defects that have occurred near surface 101f of primary metal compact 101. Furthermore, by removing surface 101f of primary metal compact 101 to a thickness T of 1.0 mm or less, the time required for machining to remove surface 101f can be reduced. This allows defects that have occurred near surface 101f of primary metal compact 101 to be efficiently removed.

[0043] (3) A third aspect of the method for producing a titanium alloy formed body is the method for producing a titanium alloy formed body of (1) or (2), wherein in the step S3 of performing the HIP treatment, the HIP treatment is performed in a temperature range of 830°C or higher and 870°C or lower.

[0044] As a result, in step S3 where HIP treatment is performed, by performing HIP treatment in a temperature range of 830°C or higher and 870°C or lower, it is possible to more effectively remove internal defects while suppressing coarsening of crystal grains in the secondary metal molding 102.

[0045] (4) A fourth aspect of the method for producing a titanium alloy formed body is the method for producing a titanium alloy formed body according to any one of (1) to (3), wherein in the step S1 of forming the primary metal formed body 101, The primary metal compact 101 is formed to have a relative density of 99.8% or more.

[0046] As a result, in step S1 of forming the primary metal compact 101, a primary metal compact 101 having a relative density of 99.8% or more is formed, thereby obtaining a primary metal compact 101 with reduced internal defects and a high relative density. Using such a primary metal compact 101 as a base, by grinding the surface 101f and applying HIP treatment, a titanium alloy compact that ensures both fatigue strength and mechanical strength can be efficiently manufactured.

[0047] (5) A fifth aspect of the method for producing a titanium alloy formed body is any one of the methods for producing a titanium alloy formed body according to (1) to (4), In the step S1 of forming the primary metal compact 101, The primary metal compact 101 is formed using a powder bed fusion process.

[0048] As a result, defects are likely to occur near the surface 101f of the primary metal compact 101 formed using powder bed fusion. By performing HIP treatment after grinding the surface 101f of such a primary metal compact 101, it is possible to ensure both fatigue strength and mechanical strength in a titanium alloy compact formed using powder bed fusion, which is likely to have defects near the surface 101f.

[0049] (6) A sixth aspect of the method for producing a titanium alloy formed body is any one of the methods for producing a titanium alloy formed body according to (1) to (5), In the step S1 of forming the primary metal compact 101, As the titanium alloy, a Ti-6Al-4V alloy is used, which contains titanium (Ti) as the main alloy and at least aluminum (Al): 5.5 to 6.75 mass % and vanadium (V): 3.5 to 4.5 mass %.

[0050] This ensures both fatigue strength and mechanical strength in a titanium alloy formed product using the Ti-6Al-4V alloy. [Explanation of symbols]

[0051] 101…Primary metal molded body 101f…Surface 102…Secondary metal molded body 103...Titanium alloy compact B...Laser beam K...Defect M…Metal powder P…Powder bed T...Thickness

Claims

1. forming a primary metal body by an additive manufacturing process using a metal powder made of a titanium alloy; removing a surface of the primary metal body by machining to a thickness equal to or greater than a predetermined dimension to obtain a secondary metal body; The method includes a step of subjecting the secondary metal compact to a hot isostatic pressing (HIP) treatment in a temperature range of 800° C. or more and 890° C. or less. A method for producing a titanium alloy compact.

2. In the step of obtaining the secondary metal molded body, the surface of the primary metal molded body is removed to a thickness of 0.1 mm or more and 1.0 mm or less. The method for producing the titanium alloy compact according to claim 1.

3. In the step of performing the HIP treatment, HIP treatment is performed at a temperature range of 830°C to 870°C. The method for producing a titanium alloy formed body according to claim 1 or 2.

4. In the step of forming the primary metal body, forming said primary metal body having a relative density of 99.8% or greater; The method for producing a titanium alloy formed body according to claim 1 or 2.

5. In the step of forming the primary metal body, forming the primary metal compact using electron beam powder bed fusion; The method for producing a titanium alloy formed body according to claim 1 or 2.

6. In the step of forming the primary metal body, As the titanium alloy, a Ti-6Al-4V alloy is used, which contains titanium (Ti) as a main alloy, aluminum (Al): 5.5 to 6.75 mass%, and vanadium (V): 3.5 to 4.5 mass%. The method for producing a titanium alloy formed body according to claim 1 or 2.

Citation Information

Patent Citations

  • Hip processing method of magnesium casting, and gearbox of helicopter formed by using hip processing method

    JP2016112580A

  • Titanium-based alloy member, method for manufacturing titanium-based alloy member, and product manufactured using titanium-based alloy member

    JP2019073760A